Neonatal gastric perforation: Our experience and important preoperative and intraoperative caveats to prognosticate and improve survival - Saurabh Shyam Garge; Geetika Paliwal (Wolters Kluwer Medknow Publications, 2020)
Aim: Neonatal gastric perforation (NGP) is a rare, perplexing, life-threatening entity affecting neonates. We share our experience of operating upon cases of NGP s and highlight important points observed which may aid in further improving care of neonates, diagnosed with this entity. Materials and Methods: A retrospective analysis of all consecutive patients with NGP operated by the author, at various centers between January 2015 and December 2018, was carried out. We analyzed different variables for these and reached logical conclusions. Results: Between January 2015 and December 2018, we treated ten patients with gastric perforation. All the neonates were preterm, except one. Mean birth weight in our series was 1745 g (range 1300-2400 g). Deterioration in activity, worsening of sepsis, metabolic acidosis, increased ventilator requirements, and abdominal distension were prominent clinical features identified in all patients. All patients subsequently had massive pneumoperitoneum before surgery. Six patients had perforation along the greater curvature, two had perforation at the posterior wall, and two had near total gastric necrosis. We had four mortalities out of ten patients operated. Conclusion: NGP is associated with high mortality, especially in premature and low birth weight neonates. Severity of contributing factors in a premature predisposed neonate determines the severity of gastric necrosis, which in turn is an important prognostic factor. Certain preoperative signs can be useful and can aid in initiating preventive measures to curtail severity of the pathology.